The Pragmatics of Nigerian English in Chimamanda Ngozi Adichie's Novels - Romanus Aboh; Happiness Uduk (National Research University Higher School of Economics, 2016)
There are relatively few studies that have examined the pragmatization of Nigerian English in Adichie's novelistic oeuvre. This study seeks to fill that gap by undertaking a pragmatic analysis of Nigerian English in Adichie's Purple Hibiscus, Half of a Yellow Sun and Americanah in order to account for the pragmatic relation between utterances and meaning explication. The theory adopted for this study is pragmatic context. The analysis indicates that the use of English as reflected in the novels is pragmatically oriented which, by and large, helps elucidate the particular use of English in the non-literary situation in Nigeria. Also, the analysis demonstrates that the contexts, in which these Nigerian English expressions occur, significantly, draw from Nigeria's sociocultural milieu, and the sociocultural milieu shapes the meaning or sense discourse participants squeeze out of utterances in interactive situations.